Analisis Suasana Café, Kualitas Produk dan Persepsi Harga terhadap Kepuasan Pelanggan di café Masalalu - Widi Apriliya; Efiani (BULLET : Jurnal Multidisiplin Ilmu, 2023)
With the times and the emergence of coffee shop businesses in Indonesia, now a favorite drink among young people, café businesses must be able to compete with their competitors or business rivals by providing the best service, and also think about strategies to be able to attract consumers. The purpose of this study was to analyze the atmosphere of the café, price perceptions, and product quality and their impact on customer satisfaction at the Masalalu Rawa Domba café. The population is all people who visit Masalalu cafe, and the sample is people who have visited 2 times or more. The number of samples taken was 120 respondents, the techniques used are purposive sampling. The results show that the influence of the cafe atmosphere, product quality and also price perceptions simultaneously influence customer satisfaction.